Dr. Muhammad Lutfi al-Sabbagh’s Approach - may God have Mercy on Him - in Calling for Islamic Morals - Hajar Matar Abd; Mashaan Muhi Alwan (International Journal of Medical Toxicology and Legal Medicine, 2024)
This research reviews the approach of Dr. Muhammad Lutfi Al-Sabbagh - may God have mercy on him - in calling for Islamic ethics, and aims to establish ethical principles among all people and preachers to God Almighty in particular, and to promote Islamic values ​​in society, and to build a society characterized by cooperation and respect. Al-Sabbagh’s methods - may God have mercy on him - varied to spread Islamic values ​​and ethics, most notably writing, and taking advantage of the media and books to spread his ideas, targeting preachers. He relied on his approach as a basic element in building the Muslim personality, and he called for strengthening moral values ​​such as patience, sincerity, contentment, generosity and humility. He used Islamic references from the Holy Quran and the Noble Hadith as a basis for understanding Islamic ethics. In conclusion, the research shows that the approach of Dr. Muhammad Lutfi Al-Sabbagh - may God have mercy on him - was comprehensive and effective in calling for Islamic ethics, which resulted in an impact on society.